Contribution to the studies of Community competition law in west Africa : Case of West African Economic and Monetary Union and Economic Community of West African States - (:unkn) unknown (My University, 2018)
West African states have made economic integration the preferred way to deal with the challenge of economic development in an increasingly competitive international context. Thus, through regional and subregional organizations, the protection of the free movement of competition has become a community issue.West African regional economic integration has therefore been seized by competition law. From this, we note emerging competition rights in the West African Economic and Monetary Union (WAEMU) and the Economic Community of West African States (ECOWAS). Each of these organizations has therefore put in place a competition law in its economic area. As a result, given the composition of UEMOA and ECOWAS, these Community rights are intended to be applied to the Member States of the Union which are also part of the Community. The features of the coexistence of these Community competition law in West Africa deserved to be examined in order to evaluate their application, to analyze the effectiveness and efficiency of these rights. This comparative study intends to highlight the contain of these rights, reveal their specificities, while showing their lacks. It’s necessary to rethink or even reform some aspects of these rights to improve their applications, basis for a better protection of free competition in West Africa.
Keywords: African Research